Influence of quartz types on mechanical parameters in the early silurian Longmaxi shale, Sichuan Basin - Qin Zhang; Feng Liang; Qun Zhao; Wen Liu; Weiliang Kong; Wanli Gao; Xinyu Zhang; Guangyin Cai; Tianquan Qu; Zhen Qiu (Scientific Reports)
Abstract Quartz is one of the most abundant minerals in shales, occurring predominantly in three forms: biogenic quartz (BQ), detrital quartz (DQ) and clay-transformed quartz (CTQ). The content of quartz is typically correlated with the fracability of shale gas reservoirs. However, the origins of quartz and its influence on mechanical properties remain not fully elucidated. To address this gap, this study examines shale samples from LM1-LM8 graptolite zones in well W202 of the Weiyuan shale gas field, the Sichuan Basin as the research object. After systematic analysis of organic geochemistry, mineral composition, cathodoluminescence observation, major/trace elements, and log interpretation and calculation of shale mechanical parameters, the genetic mechanism of quartz was analyzed and the percentage of quartz of different origins and the influence on rock mechanical properties were evaluated quantitatively. The results indicate that the three types of quartz (BQ, DQ and CTQ) were variably present in the Longmaxi shale across different graptolite zones. The LM1-LM3 graptolite zones exhibit the highest abundance of BQ, with contents ranging from 58.3 to 79.6%, with an average of 65.7%. DQ predominates in the LM4-LM5 and LM6-LM8 graptolite zones, with average contents of 38.7% and 34.9%, respectively. The BQ content is marginally higher in the LM4-LM5 zone compared to the LM6-LM8 zone, averaging 12.7% and 6.1%, respectively. The three types of quartz exert a dual influence on Young’s modulus, and a single linear effect on Poisson’s ratio. An increase BQ content correlates with a decreased in Poisson’s ratio, whereas increased contents of DQ and CTQ correlate with an increased Poisson’s ratio. With the highest Young’s modulus and the lowest Poisson’s ratio, the LM1-LM3 shale is the most favorable interval for hydraulic fracturing. Furthermore, BQ is positively correlated with the Brittleness index (BI), whereas the contents of DQ and CTQ are negatively correlated with BI. When the quartz content falls between 52% and 85%, the ratio of DQ to BQ is optimal for fracture development coinciding with high BI values, which are most conducive to fracturing stimulation.